2018
DOI: 10.15562/ism.v9i2.162
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of preeclampsia and eclampsia in Sanglah General Hospital from March 2016 to March 2017

Abstract: Background: Preeclampsia and eclampsia have been increasing at an alarming rate. It is a challenging task for doctors and pregnant mothers. Preeclampsia defined as new onset of hypertension (≥140mmHg systolic or ≥90mm Hg diastolic on at least two occasions 6 hours apart) and proteinuria (at least 1+ on dipstick or ≥300mg in a 24-hour urine collection) after 20 weeks of gestation. Eclampsia defined as neurologic involvement in the form of generalized tonicclonic convulsions in women with preeclampsia is termed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It was consistent with the findings of Grum et al where primigravida is a risk factor for preeclampsia and eclampsia in addition to multiple pregnancies, a history of preeclampsia, and alcohol consumption during pregnancy [36]. A study by Vincent et al also showed that the highest cases of preeclampsia and eclampsia occurred in primigravida women [37].…”
Section: Discussionsupporting
confidence: 90%
“…It was consistent with the findings of Grum et al where primigravida is a risk factor for preeclampsia and eclampsia in addition to multiple pregnancies, a history of preeclampsia, and alcohol consumption during pregnancy [36]. A study by Vincent et al also showed that the highest cases of preeclampsia and eclampsia occurred in primigravida women [37].…”
Section: Discussionsupporting
confidence: 90%
“…This can lead to failure of spiral artery remodeling. Blood flow to the uteroplacental will decrease and cause hypoxia and placental ischemia (Vincent et al, 2018)…”
Section: The Relationship Between Maternal Age and The Incidence Of P...mentioning
confidence: 99%
“…Extreme maternal stress such as ≥ age 40 years has been associated with an increased risk of preeclampsia/eclampsia (Ukah et al, 2016). Extreme maternal age is a risk factor for preeclampsia and women aged 40 years have a 2-fold risk of developing preeclampsia compared to younger women (Vincent et al, 2018). In research conducted by Dekker and Robillard it was found that the risk of preeclampsia in the second pregnancy increases with maternal age (Indonesian Society of Obstetrics and Gynecology, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this complication in Iran has been announced as 0.007, and this rate is increasing. Women suffering from this complication have hormonal changes (63,64). The maternal estrogen level decreases during this complication.…”
Section: Preeclampsiamentioning
confidence: 99%